Annual Technical Meeting 1996
DOI: 10.2118/96-106
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Oil Sands Industry Wastes

Abstract: Potential applications of oil sands industry wastesMajid, A.; Kotlyar, L.; Sparks, B. D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The oil sands industry generates approximately 5000 m 3 of waste material per 1000 m 3 of synthetic crude oil daily; 2500 m 3 of this waste material is associated with fluid fine tailings and mature fine tailings (MFT) (Majid and Sparks, 1999). Approximately 750 million m 3 of MFT has accumulated in tailings ponds in the Alberta oil sands region (Smith, 2011).…”
mentioning
confidence: 99%
“…The oil sands industry generates approximately 5000 m 3 of waste material per 1000 m 3 of synthetic crude oil daily; 2500 m 3 of this waste material is associated with fluid fine tailings and mature fine tailings (MFT) (Majid and Sparks, 1999). Approximately 750 million m 3 of MFT has accumulated in tailings ponds in the Alberta oil sands region (Smith, 2011).…”
mentioning
confidence: 99%
“…© 2021 The Authors. Journal of Environmental Quality © 2021 American Society of Agronomy, Crop Science Society of America, and Soil Science Society of America materials, such as water, sand, clay, petroleum coke, tailings, and/or residual bitumen (Majid & Sparks, 1999). Petroleum coke is a high-carbon-content solid produced during hydrocarbon processing and is a byproduct of bitumen upgrading to synthetic crude oil; it is increasing by 6 million m 3 d −1 (Small, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Surface mining has damaged ecosystems around the world during the past century (Dhar et al., 2018) and produced large quantities of waste materials. Oil sands mining and bitumen extraction in Canada generate thousands of cubic meters of waste materials, such as water, sand, clay, petroleum coke, tailings, and/or residual bitumen (Majid & Sparks, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing worldwide demand in crude oil leads to a steady increase in the amount of waste byproducts generated by the petroleum industry including coke, fly ash, and water tailings (Allen 2008a, b;Majid and Kotlyar 1999;Malekshahian and Hill 2011). Petroleum coke (PC) is generated in large quantities during the oil refinery process when the ratio of H:C has to be upgraded (Speight 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The PC-treated OSPW required less ozone doses to remove the remaining organics, and the resulted water was more biodegradable ). Majid and Kotlyar (1999) showed that PC reduced the concentration of total dissolved carbon from 300-600 to \50 mg/ L during the removal of free phase bitumen from wastewater by agglomeration.…”
Section: Introductionmentioning
confidence: 99%